185 A Review of the Systemic Medical Complications Following Joint Replacement. (19th August 2022) - Curlewis, K; Leung, B; Thornhill, C; Sinclair, L; Chan, G; Ricketts, D
Abstract: Aim: Arthroplasty procedures are commonly performed in the UK. For each procedure informed consent is required. To obtain informed consent the patient and their surgeon should discuss the risks and benefits of the proposed operation, including complication rates. In the literature the regional complications of arthroplasty are generally well documented. The systemic medical complications are less well described. This lack of accurate data could make it difficult for the treating surgeon to obtain valid consent. The aim of this paper was to review and compare the literature regarding the rate of systemic medical complications after common arthroplasty procedures. Method: A literature search was conducted using the PubMed, Cochrane Library and MEDLINE databases. Studies regarding the systemic medical complications and mortality rate of joint replacement published within the last 10 years were included. Any studies focusing purely on regional complications, non-English language or with no full text available were excluded. Results: We found that systemic complications were more frequent than regional complications following arthroplasty. The systemic complication rates were hip: 5.1%, knee: 6.9%, ankle: 3.0%, shoulder: 11.2%, elbow: 8.5% and wrist: 0%. The most common systemic medical complication following arthroplasty was venous thromboembolism. Pre-operative co-morbidity was the most important risk factor for both post-operative mortality and systemic medical complications following arthroplasty procedures. Conclusions: We recommend that to obtain informed consent for arthroplasty procedures, the given rates of systemic medical complications of joint replacement should be discussed and documented.